Kebijakan Perencanaan Kurikulum Pengembangan Soft Skill untuk Internalisasi Budaya Humanis dan Karakter di Perguruan Tinggi Vokasi Kedinasan - Barkah, Taopik; Hernawan, Asep Herry (Jurnal Pendidikan Indonesia, 2025)
Violence committed by seniors against juniors occurs when students are doing activities in the educational environment. The concept of a humanistic education curriculum through a parenting pattern based on the development of soft skills and character in vocational higher education needs to be planned so that acts of violence in vocational higher education. This study aims to analyze the planning of a humanistic curriculum through a parenting pattern based on the development of soft skills and character in the vocational higher education environment of the Ministry of Transportation. This study uses a descriptive qualitative approach. The research procedure involves collecting data through document studies, including journals, scientific articles, and official government documents related to the research topic. The subject of the study is a policy document related to the soft skills development curriculum in the vocational higher education of the Ministry of Transportation. Data analysis was carried out descriptively. The findings show that the formation of soft skills that must be carried out by caregivers to students/cadets consists of two activities, namely embedded and stand-alone methods. Embedded activities are carried out according to the student's daily activities. At the same time, the stand-alone method is carried out through certain activities aimed at inspiring or instilling soft skills. Therefore, curriculum planning by adding humanistic and character-based learning activities must be carried out in an integrated, structured, planned, hierarchical manner with the proper methods.